Features of the introduction of distance education for students of humanitarian specialties - Kuruch, A. (Problems of Engineer-Pedagogical Education, 2023)
The organization of distance learning in Ukraine is considered in the article. The analysis of the distance learning process is made. Researchers' views on distance learning and its conditions are analyzed. The legal framework regulating the process of distance learning is considered. The advantages of distance learning are highlighted, including opportunities to create an interactive environment in the learning process; the possibility of introducing the latest pedagogical and psychological aspects in the learning process; the possibility of learning at a convenient time and place, for all participants in the process, and no time limit for learning the material. Disadvantages of distance learning are highlighted, including the additional amount of work for teachers, the difficulty of choosing a platform to meet the interests of all participants in the process. Disadvantages also include the development of activities and texts which should meet the needs of students in the content of different disciplines. The decisive role of students' independent work as a necessary condition for professional development of a specialist is determined. It is substantiated that during distance learning there are more opportunities for conducting classes interactively – in the learning process there is an active interaction between all participants, which increases motivation to learn and improves the level of knowledge. The article analyzes popular online platforms that are actively used in distance learning by higher education institutions. It is concluded that distance learning is not suitable for the formation of teamwork skills and this form of learning is primarily suitable for self-disciplined and motivated students who are ready to work for results. The possibility of creating virtual laboratories that will help to thoroughly study the process of distance learning and improve it is analyzed. It was also concluded that IT specialists, who will be able to help teachers in the process of distance learning, will be involved.